Diseño de un sistema fotovoltaico de riego para la empresa agrícola cactus s.a. (2022)
The main objective of the research developed is to propose the design of a photovoltaic irrigation system with automated solar energy. The study was based on descriptive research for the analysis of solar characteristics and their possible use in an area of influence defined as farm 2 of the agricultural company El Cactus S.A. in Toca-Boyacá. In the first instance, the approach was given from 4 phases, which include 1). Identify the solar irradiation potential present 2). Definition of technical criteria for crops 3). Sizing of the photovoltaic system 4). Cost estimation. The analysis of secondary information consulted from related research, articles, meteorological databases, followed by primary sources such as georeferencing and demarcation, processes, production characteristics, company logs, records of electricity consumption, quotations and technical data sheets of irrigation pumps.